Evaluación preliminar de dos tipos de dieta en la especie endogea Aporrectodea trapezoides (Dugés, 1828) (Oligochaeta, Lumbricidae) - Masin, Carolina Elisabet (2012)
This study assessed Aporrectodea trapezoides capacity for their use in vermicomposting technology because numerous studies have demonstrated the suitability of earthworms to in organicwaste treatment. As food source,we considered two types of diet treatments:Diet Iwith pure (3:3) ground dried cow dung and Diet II with dried cow manure and domestic vegetable waste (1:3). The variables: behaviour, biomass, number of clitellates and cocoons at 40 and 60 days of experience were evaluated. Biomass was significantly higher (p <0.05) in heterogeneous organic substrate (Diet II) compared to a simple diet (Diet I). Bioaggregates and cocoons production in Diet I earthworms were higher than under Diet II treatment.